Feasibility of targeting canine soft tissue sarcoma with MR-guided high-intensity focused ultrasound. (1st January 2019) - Seward, Marion C.; Daniel, Gregory B.; Ruth, Jeffrey D.; Dervisis, Nikolaos; Partanen, Ari; Yarmolenko, Pavel S.
Abstract: Purpose: Magnetic resonance imaging-guided high-intensity-focused ultrasound (MR-HIFU) is a non-invasive treatment modality that precisely focuses ultrasound energy within a tumour and can be customised to result in a wide range of local bioeffects. The purpose of this study was to determine the feasibility of using MR-HIFU to treat soft tissue sarcoma (STS) in dogs. Materials and methods: Medical records of dogs admitted to the Virginia-Maryland College of Veterinary Medicine from 1 January 2012 to 31 December 2016 were searched for a diagnosis of sarcoma with available cross-sectional imaging of the tumour (MRI or CT). Fifty-three (53) dogs were eligible for inclusion. Tumor tissue (in bone as well as in soft tissue) was considered targetable unless: (1) the ultrasound path was completely obstructed by bone or gas and (2) the MR-HIFU target was within the spinal cord or less than 1 cm from the margin of the spinal cord. Tumors were categorised as <50% targetable, ≥50% targetable or non-targetable. Results: Eighty-one percent of STS (81.1%, 43/53) were targetable. The head/spine tumour sites had the highest proportion of non-targetable tumours (36%, 9/25). The majority of truncal and axillary tumours were ≥50% targetable (88.9%, 16/18), and all extremity tumours were considered ≥50% targetable (100%, 5/5). Conclusions: The majority of STS were targetable. This is the first study to evaluate MR-HIFU targetability of canine STS. HIFU has potential as a therapeutic modality for treating STS in dogs, and this veterinary application is a possible model for treatment of naturally occurring STS in humans.